The evidence base for WHS priority setting in a changing work landscape: an appraisal of sources and opportunities for enhancement. (2nd April 2020) - Bluff, Elizabeth; O'Keeffe, Valerie
ABSTRACT: This review paper contributes to literature on the changing nature of work and its implications for regulating work health and safety (WHS). The paper aims to examine how Australian WHS agencies can enhance their evidence base for setting priorities, in the context of trends in business size and structure, industry and work, unionisation, work arrangements and worker attributes. The paper maps key trends and incorporates these in a conceptual framework for appraising data and information sources for priority setting, as identified through searches of literature databases and websites of WHS agencies. With reference to this conceptual framework, the paper examines a range of regulator, compensation, coronial, health and labour datasets. Principal findings are: the greater strength of information about traumatic deaths, injuries and their causes compared with information about slower onset diseases and conditions; the limited basis for differentiating business WHS performance and worker experiences by key business and workforce trends; under-representation of vulnerable workers' experiences; and the retrospective focus of many sources. The paper concludes that to enhance their evidence base, WHS agencies will need to build analytical expertise and/or links with research bodies and carefully select, extend and combine sources.